The Effect of Riddle Teaching Technique on The Eleventh Grade Students’ Vocabulary Mastery at SMK Swasta GKPS 2 Pematangsiantar - Nadya Bersista E Marbun; Partohap Saut Raja Sihombing; Novra Melisa P. Hutabarat (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2024)
The aim of this study is to assess the impact of the Riddle Teaching Technique on vocabulary mastery among eleventh-grade students at SMK Swasta GKPS 2 Pematangsiantar. The research employs a quasi-experimental design to gauge the effectiveness of this technique in enhancing students' vocabulary skills. The research population comprises 75 eleventh-grade students from SMK Swasta GKPS 2 Pematangsiantar. The sample is divided into two groups: the experimental group (XI TKR) with 30 students who employed the Riddle Teaching Technique, and the control group (XI TBSM) with 30 students who followed conventional learning methods. Data were gathered through writing tests administered as pre-tests and post-tests. The analysis was conducted using SPSS Version 26, which included descriptive analysis, tests for normality, the Wilcoxon test, homogeneity tests, and the Mann-Whitney test. The analysis results, particularly from the Mann-Whitney test, revealed an Asymptotic Significance (2-tailed) value of 0.025, which is less than the threshold of 0.05. This indicates that the alternative hypothesis (Ha) is accepted while the null hypothesis (Ho) is rejected. Therefore, it concludes that the Riddle Teaching Technique has a significant positive effect on the vocabulary mastery of eleventh-grade students at SMK Swasta GKPS 2 Pematangsiantar.